Transformation of Kampar Manuscript Illuminations into Batik Motifs - Iik Idayanti; Jefrizal Jefrizal; Deni Afriadi (Fakultas Bahasa Seni dan Budaya, 2025)
This article discusses the transformation of Kampar manuscript illuminations into batik motifs as an effort to preserve Malay cultural heritage. Manuscripts are written sources that contain cultural values, knowledge, and aesthetics, including illuminations that reflect local identity. The method used in this research is a qualitative descriptive method. The material sources focused on in this research are two Kampar manuscripts obtained through the British Library's Endangered Archives Programme (EAP), namely manuscripts with codes EAP1020/3/6 and EAP1020/5/1. Both manuscripts have illuminations in the form of Kaluk Paku (fern) and Pucuk Rebung (bamboo shoot) motifs, which are then transformed into batik motifs. The research results show that the Kaluk Paku motif produces a batik motif named Pakis Bersusun (Stacked Fern), symbolizing the values of friendship and mutual support. Meanwhile, the Pucuk Rebung motif produces a batik motif named Pucuk Rebung Melingkar (Circular Bamboo Shoot), depicting the spirit of unity and togetherness. It is hoped that the results of this transformation can become part of the local creative industry and enrich the cultural heritage of Kampar.